Living on the Edge of Risk: Representations of Suicide among Students of Vocational Training at the National Police Academy (Brazil) - Almeida, T.; Oliveira, A. (Exploring Ethnographic and Non-Ethnographic Approaches of Suicide and Self-Harm, 2015)
Death is always difficult to face, but in the cases of suicide it is even harder because death was self-inflicted. Suicide is usually seen as a solution, a response to the collapse of hopes, plans and expectations. It is always quite difficult to understand and assimilate why it happens. In particular the death by suicide is complex, and surrounded by fear and taboo. Especially among the police officers, generally seen as cold, strong, very well equipped and living in frequent danger, ready for all situations, it is disturbing to imagine that they are capable of such an extreme act. Although the profession of police officer seems to be tied to the strength—and we must behold the police is the institution nowadays authorized by society to use force legitimately for the maintenance of order, essential for the exercise of individual rights—the occurrence of voluntary deaths among these professionals is significant, especially if we consider that this is a population psychologically and physically tested. Despite suicide is an uncommon event, the impact on suicide survivors, mainly in the co-workers is significant. Above all in closed occupational groups, such as police officers, the effects of suicide beget anxiety, uncertainty and doubts. We may estimate that about six people are seriously distressed for each suicide that occurs. The present research aims, first of all, to analyse the representations of suicide among future Brazilian Federal Police—students of vocational training at the National Police Academy (Brazil). After a preliminary study, that included a semi-structured interview, we obtained important items which supported the questionnaire—that after developed was administered to almost 500 recruits—in which we examined, among others, the dimensions of thoughts, feelings and images about suicide and the reasons considered most relevant for choosing the profession. After analyzed the answers, according to the gender and age, we found relevant representations, in order to understand some contexts in which a death by suicide may happen.